K-popfication in the Indonesian Political Arena: The Phenomenon of @aniesbubble on X - Andina, Tri Kurnia Revul; Ikrima, Nabila; Akalili, Awanis; Adikara, Gilang Jiwana; Setiawan, Benni (Jurnal Pemikiran Sosiologi, 2025)
Political years in Indonesia have always presented new and unexpected occurrences, including campaign strategies and activities of candidate supporters. Social media has played a significant role in shaping these patterns due to its ability to mobilize the community. One of the campaigns in the 2024 presidential election was the @aniesbubble account on X, a supporter of presidential candidate 01 Anies Baswedan. When it first appeared, this account drew widespread attention for its similarities to a Korean Pop (K-Pop) fan account. Anies was portrayed as an idol, while @aniesbubble is a fan account dedicated to sharing updates and information about him. Other accounts affiliated with @aniesbubble: @olpproject, and @haveniesday further amplified this strategy. This study aims to examine the 'K-popfication' (K-pop-inspired communication) of the content produced by the three accounts on X. This study employs a qualitative content analysis method to see the elements of 'K- popfication' in tweets or messages published within December 2023 and February 2024. The results reveal significant elements of ‘K-popfication’,, signaling a new era in Indonesian politics, defined by the pervasive use of social media and a more proactive and participatory audience dynamic. In addition, this research shows that the communication aspect was reflected in the creative use of social media and political support for Anies Baswedan and Muhaimin Iskandar was reflected in various online and offline activities. Lastly, thses accounts played crucial roles in spreading information about the candidates as they gained early access to information by attending and participating in Anies and Muhaimin’s events.